E-Commerce as New Concepts in 4.0 Era - Soegoto, Eddy Soeryanto; Alfian, Faridz (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This research aims to develop new concepts in IT-based business as an idea of an online business venture that has been widespread in the world. This research used mix methods. Qualitative explanation based on a literature study. This research can be used as a reference for developing new concepts in IT-based businesses to increase customer interest and convenience. This new concept can be used for online business entrepreneurs in creating and developing a newer IT-based online business or system. This research was based on journal references and subjective assessments as users of online business applications, and especially online shop which shows that online business shop competition continues to compete and develop in providing new features for the convenience of its users. The results of this study are created new ideas that are unique, creative, effective, efficient, providing benefits and ease of use.